Investigating the Influence of Human Resource Management Practices on the Performance of Tertiary Institutions in South-western Nigeria - James, Odumeru; Fagbenle, Ayoola (Acta Universitatis Danubius. Œconomica, 2025)
TIs have the potential of playing significant role in the socio-economic development of any society. The same is true of Nigeria. Sadly, performance of Tertiary institution (TIs) in Nigeria has been on a downward spiral in recent years. Additionally, the study of the relationship and transmission mechanism between Human Resource Management (HRM) practices and performance of TIs in Nigeria is sparse in literature. This study investigated the role of HRM practices on the performance of TIs in South-western Nigeria, and the mediating impact of employee commitment and job satisfaction in the relationship. To meet these objectives, cross-sectional survey research design was adopted. Data measuring key dimensions of HRM practices (Recruitment and selection, training and development, performance appraisal, and compensation management) performance of TIs (perceived quality of tertiary education and perceived relevance of TIs), job satisfaction and employee commitment was collected from 390 academic staff members, which were selected a population of 9,817 academic staff members of selected public and private owned polytechnics in South-western Nigeria via stratified and purposive sampling technique. Sample size was determined using the Taro Yamane formula at 5% level of significance. Analyses was carried out using Partial Least Square Structural Equation Modelling. Results shows that all 4 dimensions of HRM practices have pat coefficients of greater that ±0.1 at p < 0.05 indicating dimensions of HRM practices determine both perceived quality and perceived relevance of tertiary education in South-western Nigeria. Also, it was discovered employee commitment and job satisfaction do not significantly mediate the HRM practices -TI performance relationship with path coefficients ranging from -0.1 to +0.1 at p < 0.05. The coefficient of determination at 0.3 and above further strengthens the conclusion that the relationships are significant. This investigation therefore concluded that there exists a direct relationship between HRM practices and performance of TIs. Based on this outcome, it was recommended that owners and policy makers of TIs should pay attention to all dimensions of HRM practices in order to optimize the performance of their various institutions.